2018
DOI: 10.1186/s13054-018-2178-7
|View full text |Cite
|
Sign up to set email alerts
|

A complete and multifaceted overview of antibiotic use and infection diagnosis in the intensive care unit: results from a prospective four-year registration

Abstract: BackgroundPreparing an antibiotic stewardship program requires detailed information on overall antibiotic use, prescription indication and ecology. However, longitudinal data of this kind are scarce. Computerization of the patient chart has offered the potential to collect complete data of high resolution. To gain insight in our global antibiotic use, we aimed to explore antibiotic prescription in our intensive care unit (ICU) from various angles over a prolonged time period.MethodsWe studied all adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Given the multitude of potential sources of variation, past observational studies produced highly variable findings with excess risk estimates ranging from 0 up to 50% (5). Multi-state model (MSM) approaches for estimating mortality and prolonged stay due to HAIs have been widely advocated in recent years as they aid in avoiding common types of bias (5)(6)(7). Their focus on a specific effect measure, the time-dependent populationattributable fraction (PAF), may moreover reduce variability in findings due to various definitions of excess risk.…”
Section: Abstract Word Count: 250mentioning
confidence: 99%
“…Given the multitude of potential sources of variation, past observational studies produced highly variable findings with excess risk estimates ranging from 0 up to 50% (5). Multi-state model (MSM) approaches for estimating mortality and prolonged stay due to HAIs have been widely advocated in recent years as they aid in avoiding common types of bias (5)(6)(7). Their focus on a specific effect measure, the time-dependent populationattributable fraction (PAF), may moreover reduce variability in findings due to various definitions of excess risk.…”
Section: Abstract Word Count: 250mentioning
confidence: 99%
“…Recently, De Bus et al described the system used in the Ghent University Hospital ICU. ( 26 ) Antibiotic prescription data were prospectively merged with diagnostic and microbiology data by ICU physicians through dedicated software during a 4-year period. Definite focus of infection and probability of infection (high/moderate/low) were reassessed by dedicated ICU physicians at patient discharge.…”
Section: Antimicrobial Stewardship Should Not Be Implemented and Perfmentioning
confidence: 99%
“…Prevalence: Several studies suggest that prophylactic administration of antimicrobials is commonly practiced in the ICU. A single-centre prospective study conducted in Belgium showed that among 10,731 antibiotic treatment courses recorded for 3 years, 42% (n = 4525) were prescribed for prophylaxis [13]. A nationwide, single-day survey conducted among 52 ICUs in Japan found that 34% (n = 331/1028) of the prescriptions for intravenous antibiotics written that day were for prophylaxis [14].…”
Section: Definitions and Prevalence Of "Prophylactic" Antimicrobial Tmentioning
confidence: 99%
“…However, SAP is also commonly practiced in many ICUs. A single-centre study conducted recently in a Belgian ICU showed that SAP and prophylaxis for immunocompromised patients constituted two-thirds of prophylactic antibiotic treatments prescribed [13]. In non-ICU patients, it is recommended that SAP be administered 30-60 min before surgical incision to enable achievement of a high serum concentration of antibiotics prior to incision [11,12].…”
Section: Indications For Antimicrobial Prophylaxis In Icu Patientsmentioning
confidence: 99%